Age of Ultron: Exploring the Transformational Leadership Influence on Marketing Innovation of SMEs (An Investigation Based on the 4I Model of Burns) - Mustafa, Muh. Yushar; Ismail, Md. Daud; Haeruddin, M. Ikhwan Maulana; Natsir, Uhud Darmawan; Idris, Muh. Ma'ruf; Akbar, Abdi; Mariñas-Acosta, Caroline (PT Smart Media Makassar, 2025)
Leadership is a critical factor in safeguarding the development of SMEs’ marketing innovation. The literature shows that the concept of transformational leadership has gained significant scholarly attention recently. However, there is a scarcity of empirical research on the role of transformational leadership style within the context of small and medium-sized enterprises (SMEs). Additionally, existing studies mainly focus on developed countries ignoring the unique contextual setting of developing countries. In line with such a phenomenon, this study addresses the research gaps by investigating the role of transformational leadership in SMEs’ marketing innovation strategy. The scope of this study is SMEs in the Makassar region of Indonesia. In addition, this study was conducted from July 2024 to February 2025. Through the analysis of the existing studies and the preceding theoretical frameworks, this study identifies several key characteristics of transformational leadership that contribute to the innovative practices of SMEs in Makassar. As such, for theoretical implications, the finding of this study suggests that transformational leadership enhances creativity, encourages risk-taking, and fosters an organisational culture conducive to innovation, ultimately driving the growth and competitiveness of SMEs in the region. For managerial implications, this study offers several insights that may be beneficial for SME owners, especially in helping SMEs to be more highly innovative.